Maternal mortality in the Middle East and North Africa region - how could countries move towards obstetric transition stage 5? - Sathyanarayanan Doraiswamy; Sohaila Cheema; Patrick Maisonneuve; Anupama Jithesh; Ravinder Mamtani (BMC, 2022)
Abstract Background Maternal mortality in the Middle East and North Africa (MENA) region decreased significantly between 1990 and 2017. This was uneven, however, with some countries faring much better than others. Methods We undertook a trend analysis of Maternal Mortality Ratios (MMRs) of countries in the region in order to understand differences in reduction across countries. Data were extracted from several databases for 23 countries and territories in the region on measures of women's empowerment, availability of vehicles and human resources for health (as a proxy to the three delays model). We identified factors associated with MMR by grouping countries into five different Stages (I-V) of obstetric transition from high to low MMRs. Results Among the four Stage II countries, MMR is associated with "antenatal care coverage (% with at least one visit)" and "medical doctors per 10,000 population". Among the eight Stage III countries, MMR is associated with "Gender Parity Index in primary and secondary level school enrolment" and with "nursing and midwifery personnel per 10,000 population". Among the 10 countries and one territory in Stages IV and V, MMR is associated with "GDP per capita", "nursing and midwifery personnel", and "motor vehicle ownership/motorization rate". Two factors were associated with changes in MMR from the period 2006-2010 to 2011-2015: 1) change in adolescent birth rate (r = 0.90, p = 0.005) and 2) Gender Parity Index in primary level school enrolment (r = − 0.51, p = 0.04). Conclusion Though impressive reductions in MMR have been achieved across countries in the MENA region since 1990, governments should realize that there exists an opportunity to learn from each other to bring MMRs as close to zero as possible. Immediate steps in the right direction would include investment in human resources for health, particularly nurses and midwives; measures to improve adolescent sexual and reproductive health; and greater investments in achieving gender equity in education.